Os efeitos da leitura dialógica sobre a aquisição de habilidades pré-matemáticas em pré-escolares - Faggian, Alana (Universidade Federal de São Carlos, 2021)
Although mathematical knowledge is essential for the individual's autonomy and independence, allowing the resolution of everyday problems, we observe a critical condition about the level of learning in Mathematics, especially in Brazil, where 68.1% of Brazilian students are at the worst level of proficiency in mathematics according to the latest PISA assessment. One of the causes of this scenario may be the failure to acquire pre-mathematical skills. These include subitization, number sense, counting, measuring, and other relations, and are singled out by a vast array of empirical studies as predictors of more complex mathematical skills such as addition and subtraction. Understanding storytelling as a potential strategy for teaching these skills in the preschool period, enabling contextualized and meaningful learning for the child, the objective of this research is to verify the effects of storytelling combined with a children's book, based on Dialogic Reading categories on the performance of pre-mathematical skills in two preschoolers. The mathematical relations included were: larger/smaller (size), inside and outside (spatial), more and less (quantity), and dictated number-quantity. A single-subject design was adopted, with pre- and post-tests set in MTS. The results showed improvement in post-training performance in all relations and both participants, except for the relations less for one participant, and the dictated number-quantity relations, in which the performance was not changed, due to a high initial repertoire of both participants. Limitations generated by the pandemic context and limitations arising from the design are considered. Possibilities for unfolding and continuing investigations around storytelling for the acquisition of pre-mathematical repertoires are presented at the end of the study.
The effects of dialogic reading on the acquisition of pre-mathematical skills in preschoolers
Keywords: Contação de história; Habilidades pré-matemáticas; Pré-escolares; Matching to sample; Análise do comportamento; Storytelling; Pre-mathematical skills; Preschoolers; Behavior analysis; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL